Short-term trade-offs of organic matter management strategies for smallholder farms - Ekyaligonza, Deous Mary; Tibasiima, Thaddeo Kahigwa; Dietrich, Phillipp; Kagorora, John Patrick; Friedel, Jürgen Kurt; Eder, Michael; Freyer, Bernhard (Frontiers in Sustainable Food Systems, 2022)
Organic matter management (OMM) strategies such as farmyard manure (FYM) application, legume integration, crop residue incorporation, and alley cropping are recognized for improving soil fertility and crop productivity. However, studies on yield and economics of a combination of such strategies on smallholder farms are generally scarce, yet an understanding of such can enhance adoption. This study analyzed the yield and gross margins of crops grown with OMM strategies in comparison to those grown under inorganic fertilizer application on smallholder farms. Field experiments with five treatments over two short rainy (SR) and two long rainy (LR) seasons were conducted from January 2018 to February 2020 on 10 smallholder farms. The treatments (T) included T1 (control): the inorganic fertilizer application strategy that involved maize monocrop with 50 kg/ha Diammonium phosphate (DAP) application and the OMM strategies (T2-T5). T2: cowpea-maize-bean-maize rotation; T3: cowpea-maize-bean-maize rotation + 2.5 tons/ha FYM; T4: Faidherbia albida alleys + cowpea-maize-bean-maize rotation; and T5: Faidherbia albida alleys + cowpea-maize-bean-maize rotation + 2.5 tons/ha FYM. The maize in T3-T5 was intercropped with Mucuna pruriens. The results indicate that the grain and residue yields in LR were not significantly different among all treatments. The total variable costs, which included monetarized labor and annualized capital costs for the establishment of F. albida were significantly higher under T1 than in T2-T5 during LR2018 and not significantly different from what was observed under T3-T5 in LR2019. The accumulated revenues and gross margins for the four seasons were not significantly different between T1 and the OMM strategies. We conclude that the integration of OMM strategies can give gross margins similar to the 50 kg/ha DAP application. Further, based on the price sensitivity analysis, we conclude that the smallholder farmers could adopt T3 and T4 as the gross margins under these treatments are less affected by grain price fluctuations than in T1, T2, and T5. Since the smallholder farmers can access the planting materials, we recommend the adoption of T3 and T4 on smallholder farms.